The role of menopausal hormone therapy in women with or at risk of ovarian and breast cancers: Misconceptions and current directions. Issue 4 (20th December 2018) - Temkin, Sarah M.; Mallen, Adrianne; Bellavance, Emily; Rubinsak, Lisa; Wenham, Robert M.
Abstract : For women who are candidates for menopausal hormone therapy (MHT), estrogen can provide relief from symptomatic menopause, decrease rates of chronic illnesses, and improve health‐related quality of life. However, confusion surrounds the evidence regarding the impact of exogenous estrogen and progesterone on the breast and ovary. Available data regarding the risks of MHT (estrogen and/or progestin) related to the development of breast and ovarian cancer are often inconsistent or incomplete. Modern molecular and genetic techniques have improved our understanding of the heterogeneity of breast and ovarian cancer. This enhanced understanding of the disease has impacted our understanding of carcinogenesis. Treatment options have evolved to be more targeted toward hormonal therapy for certain subtypes of disease, whereas cytotoxic chemotherapy remains the standard for other histological and molecular subtypes. The role of MHT in the breast and ovarian cancer survivor, as well as women who are at high risk for the development of hereditary breast and ovarian cancer, remains controversial despite evidence that this treatment can improve quality of life and survival outcomes. Through this article, we examine the evidence for and against the use of MHT with a focus on women who have or are at high risk for breast and ovarian cancer. Abstract : We summarize the evidence, in the context of menopausal hormonal therapy (MHT) in general, for and against the use of menopausal hormone therapy in women who are at high risk for hereditary breast and ovarian cancer and for women who have been diagnosed with breast and ovarian cancer. Reduced use of MHT may compromise women's quality of life and may have a negative survival impact for many.